Personal, behavioral and socio-environmental factors associated with diet quality among in-school adolescents in Kuala Lumpur - Rezali, Fara Wahida (2014)
This study aimed to determine the contribution of personal, behavioral, and socio-environmental factors towards the diet quality among in-school adolescents in Kuala Lumpur. This study was conducted in three selected secondary schools in Kuala Lumpur. This study is a cross-sectional study design in which multi-stage sampling was used for the selection of respondents. The diet quality of respondents was assessed using the Healthy Eating Index for Malaysians (HEI for Malaysians). The personal factors, particularly body image, self-efficacy for healthy eating, and nutrition knowledge of the respondents were assessed using Multi-dimensional Body Image Scale (MBIS), self-efficacy for healthy eating scale from the Project EAT Survey, and nutrition knowledge questionnaire adapted from the Dietary Questionnaire on Food Habits, Eating Behavior, and Nutritional Knowledge, respectively. The behavioral factors, particularly eating behaviors, dietary intake, and physical activity of the respondents were assessed using the Eating Behaviors Questionnaire (EBQ), 2-day Dietary Recall, and 2-day Physical Activity Recall, respectively. The socio-environmental factors, particularly parental role modelling of healthy eating, availability of healthy foods, and family meal frequency were assessed using the Parental Role Modelling of Healthy Eating Scale, availability of healthy foods scale from the Project EAT Survey, and EBQ, respectively. Pearson Product-Moment Correlation was used to determine the correlations between continuous variables. Independent Samples T-test, Mann-Whitney U Test, and One-Way ANOVA were used to compare the differences between the means and medians of the variables. Multiple linear regression analysis was used to determine the contribution of the independent variables on a dependent variable. A total of 373 respondents (35.1% males, 64.9% females), with a mean age of 14.3±1.2 years old participated in this study. The majority of the respondents were Malays (54.4%), followed by Chinese (34.3%), Indians (8.8%), and other ethnic groups (2.5%). The majority of the respondents (80.7%) had a high risk of poor diet quality, with a mean HEI for Malaysians composite score of 37.9±9.1%. About one in five of the respondents (23.8%) were overweight and obese, with a mean BMI z-score of 0.02±1.44. The mean composite score of MBIS among the respondents was 56.52±9.84%. The mean score of self-efficacy for healthy eating and nutrition knowledge among the respondents were 15.5±3.8 and 6.7±1.7, respectively. The mean frequencies for breakfast, lunch, and dinner consumption were 4.9±2.4 days/week, 5.8±1.9 days/week, and 5.9±2.0 days/week, respectively. The mean frequencies for morning tea, afternoon tea, and supper among the respondents were 4.2±2.6 days/week, 3.9±2.4 days/week, and 2.1±2.2 days/week, respectively. The mean frequency for eating away from home among the respondents was 2.3±1.8 days/week. The mean frequency for fast food consumption at any fast food restaurant among the respondents was 1.3±1.3 days/week, while the median frequency for take away at any fast food place was 0.0 day/week. The mean energy intake, percentages of energy from meals and snacking among the respondents were 1699±549 kcal, 61.5±22.9%, and 38.3±22.7%, respectively. The mean physical activity level value of the respondents was 1.41±0.38, indicating that the respondents were practicing a low active lifestyle. The mean score of parental role modelling of healthy eating among the respondents was 33.49±6.23. The mean score of availability of healthy foods and the mean family meal frequency among the respondents were 9.42±2.95 and 5.6±2.0 days/week, respectively. Males (34.2±8.2%) had a significantly poorer diet quality than the females (39.9±9.0%) (t=-5.941,p<0.05). Malays (36.9±8.7%) had significantly poorer diet quality than Indians (41.3±10.0%) (F=2.762,p<0.05). Diet quality of respondents decreased as age decreased (r=0.123,p<0.05). The self-efficacy for healthy eating (r=0.129,p<0.05) and availability of healthy foods (r=0.159,p<0.05) were positively correlated with the diet quality among the respondents. Being a male (t=-6.296,p<0.05), being a Malay (t=-2.716,p<0.05), and low availability of healthy foods (t=2.007,p<0.05) contributed 14.5% of the variance in poor diet quality among the respondents (F=12.486,p<0.05). Thus, programme planners should consider the differences in sex and ethnicity in implementing intervention to improve the diet quality of adolescents. The components of the availability of healthy foods should be incorporated in the future nutrition and health-related intervention programme to improve the diet quality of adolescents.